2018
DOI: 10.1038/s41598-018-35709-5
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Intravenous Gadolinium Inner Ear MR Imaging in Diagnosis of Ménière’s Disease

Abstract: This study aimed to investigate the usefulness of the intravenous gadolinium enhanced inner ear magnetic resonance imaging (IV-Gd inner ear MRI) in diagnosing Ménière’s disease(MD) and find a correlation between the degree of endolymphatic hydrops(EH) and the audiovestibular tests. Total 29 patients diagnosed with unilateral definite MD were enrolled. All patients underwent IV-Gd inner ear MRI and auditory and vestibular function tests such as pure tone audiometry (PTA), electrocochleography (ECoG), cervical v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 39 publications
2
36
1
1
Order By: Relevance
“…ECochG was reported as a valuable tool in the diagnosis of MD due to its sensitivity to the ELH ( 18 , 19 ). Cho et al reported that the vestibular ELH was larger in patients with abnormal SP/AP than those with normal results ( 51 ). Yang et al showed a correlation between SP/AP with vestibular ELH, but not with cochlear ELH ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…ECochG was reported as a valuable tool in the diagnosis of MD due to its sensitivity to the ELH ( 18 , 19 ). Cho et al reported that the vestibular ELH was larger in patients with abnormal SP/AP than those with normal results ( 51 ). Yang et al showed a correlation between SP/AP with vestibular ELH, but not with cochlear ELH ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…audiovestibular results 11 . IV-Gd inner-ear MRI is less invasive and are much more efficient because it requires less time after the injection of the contrast agent compared to the IT method (4 hr vs. 24 hr) and can evaluate both sides simultaneously 12 .…”
mentioning
confidence: 99%
“…As a result, the time required to apply pressure on the BM surface is too short to consider repeated calculation for the BM stiffness due to the gradually increased BM deformation. Furthermore, according to previous imaging studies [9, 29], there is significant deformation due to the EH in Reissner’s membrane (which is the boarder membrane between SV and SM) rather than BM. Also, according to MRI studies using 3D FLAIR sequences, EH is visualized with sensorineural hearing loss >45 dB, and this supports the hypothesis that EH will develop when medium and high frequencies are involved in MD [30, 31].…”
Section: Discussionmentioning
confidence: 89%
“…They concluded that EH is necessary but not sufficient for a display of the full triad of MD symptoms: vertigo, balance, and hearing disease. Specifically, Cho et al [9] analyzed the correlation between EH seen in MRI and various audio-vestibular tests and showed the various correlation according to each studied case. Although tests other than audiometry were not used in the diagnosis of MD, the EH of cochlea was not sufficient to account for all MD symptoms including hearing loss.…”
Section: Introductionmentioning
confidence: 99%